The Potential Benefit of Beta-Blockers for the Management of COVID-19 Protocol Therapy-Induced QT Prolongation: A Literature Review - Teuku Heriansyah; Indah Nur Chomsy; Lyra Febrianda; Tjut Farahiya Hadi; Titin Andri Wihastuti (MDPI AG, 2020)
The World Health Organization (WHO) officially announced coronavirus disease 2019 (COVID-19) as a pandemic in March 2020. Unfortunately, there are still no approved drugs for either the treatment or the prevention of COVID-19. Many studies have focused on repurposing established antimalarial therapies, especially those that showed prior efficacy against Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) and Middle East Respiratory Syndrome Coronavirus (MERS-CoV), such as chloroquine and hydroxychloroquine, against COVID-19 combined with azithromycin. These classes of drugs potentially induce prolongation of the QT interval, which might lead to lethal arrhythmia. Beta-blockers, as a β-adrenergic receptor (β-AR) antagonist, can prevent an increase in the sympathetic tone, which is the most important arrhythmia trigger. In this literature review, we aimed to find the effect of administering azithromycin, chloroquine, and hydroxychloroquine on cardiac rhythm disorders and our findings show that bisoprolol, as a cardio-selective beta-blocker, is effective for the management of the QT (i.e., the start of the Q wave to the end of the T wave) interval prolongation in COVID-19 patients.